Pengaruh Harga dan Promosi di E-Commerce Shopee terhadap Perilaku Konsumtif Mahasiswa Institut Ilmu Hukum dan Ekonomi Lamaddukelleng - Agus Purwanto; Ahmad; Andi Sumangelipu (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2025)
The development of digital technology has changed people's consumption patterns, especially among students who are active users of e-commerce. This study aims to determine the effect of prices and promotions on the Shopee platform on the consumer behavior of students in the Management Study Program at the Lamaddukelleng Institute of Law and Economics. This type of research is quantitative with an associative approach. A sample of 60 respondents was selected using a purposive sampling technique with the criteria of students who actively shop at Shopee. Data were collected through questionnaires and analyzed using multiple linear regression with the help of the SPSS program version 31. The results showed that price (X₁) had a positive and significant effect on consumer behavior with a t-value of 4.704 and a significance of 0.000 <0.05, while promotion (X₂) also had a positive and significant effect with a t-value of 3.214 and a significance of 0.002 <0.05. Simultaneously, both variables had a significant effect on student consumer behavior with an F-value of 12.430 and a significance of 0.000 <0.05. The coefficient of determination (R²) of 0.426 indicates that price and promotion can explain 42.6% of the variation in student consumer behavior, while the remainder is influenced by other factors outside the research model. The results of this study prove that Shopee's digital pricing and promotion strategies significantly encourage student consumer behavior in the digital era